Aplikasi Duckweed (Lemna sp) pada Pakan Benih Ikan Lele Mutiara (Clarias gariepinus) - Kristiana, Indra; Karisma, Ari Suci; Astiyani, Wahyu Puji; Akbarurrasyid, Muhammad; Pietoyo, Atiek (Jurusan Akuakultur, Universitas Bangka Belitung, 2022)
Pearl Catfish (Clarias gariepinus) is a type of freshwater fish that is widely cultivated by many people because of its economic value. Pearl catfish is a new strain of African catfish Clarias gariepinus Burchell, 1822 superior breeding results of the Sukamandi Fish Breeding Research Agency (BPPI) which has been declared passed in the Type / Variety Release Assessment on October 27, 2014, under the name MUTIARA (Peerless High Quality) catfish. This study aims to determine the effect of the addition of duckweed on feed on the growth and survival of pearl catfish fry. The test fish is a pearl catfish measuring 7-10 cm long and weighing 6 gr that is kept in a sized aquarium (120 cm x 50 cm x 40 cm), as many as 9 aquariums, three aquariums as a control, three aquariums for treatment A, three aquariums for treatment B, with each treatment A(5% dry duckweed), treatment B (10% dry duckweed) and treatment K (control) without treatment. . The results showed that dry dukweed can be used as an addition to fish feed, of the three feeds that provide the best growth, namely in the B treatment (10% dry duckweed) has a daily growth rate (GR) of 0.41 g, Specific Growth Rate 2,57%, absolute weight 19 g, absolute length is 11.31 cm with a survival of 90%.